Gastroprotective effects of ethanolic extract of Satureja bachtiarica against ethanol-induced gastric ulcers in rats - Firoozeh Saghaei; Abdolrasoul Namjou (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: Free radicals play an important role in the development of some diseases, including gastrointestinal ulcers. Current gastric ulcer drugs have side effects, so the tendency to use herbs and replace them with synthetic drugs has increased. In this regard, plants of the Satureja family have been studied in terms of healing and antioxidant properties. The aim of this study was to evaluate the protective effects of Satureja bachtiarica ethanolic extract on ethanol-induced gastric mucosal ulcers in rats. Experimental: Thirty rats were divided into 5 equal groups. Group 1 received 200 mg / kg of ethanolic extract of Satureja bachtiarica (EESB), group 2 received 400 mg / kg EESB, group 3 received 20 mg / kg omeprazole, group 4 received 1 mL of CMC and group 5 received 1 mL of normal saline. One hour after treatment, each animal received absolute ethanol (1ml / rat) orally by gavage. The other 30 mice were treated with oral ethanol after induction of gastric ulcer as described above, but all treatments were once a day for 14 days. At the end of both tests, ulcer index, histopathologic exams, Malonedialdehyde (MDA) and Superoxide dismutase (SOD) were measured. Results: Ethanolic extract of Satureja bachtiarica (400 mg/kg) and omeprazole had a significant effect on reducing ulcer index and increasing ulcer inhibition. It significantly preserved the gastric wall mucosa and reduced the formation of ethanol-induced gastric lesions. Also in this study a significant increase in superoxide dismutase (SOD) activity and a significant decrease in Malonedialdehyde (MDA) in gastric tissue were observed. Recommended applications/industries: The anti-ulcer effect of this plant seems to be due to the reduction of oxidative stress, which is probably due to the presence of thymol and carvacrol in the plant extract. This plant may be considered officially in the treatment and prevention of stomach ulcers in the future.